Macrophage-mediated tissue response evoked by subchronic inhalation of lead oxide nanoparticles is associated with the alteration of phospholipases C and cholesterol transporters - Smutná, Tereza; Dumková, Jana; Kristeková, Daniela; Laštovičková, Markéta; Jedličková, Adriena; Vrlíková, Lucie; Dočekal, Bohumil; Alexa, Lukáš; Kotasová, Hana; Pelková, Vendula; Večeřa, Zbyněk; Křůmal, Kamil; et al. (Particle and fibre toxicology, 2022)
BACKGROUND: Inhalation of lead oxide nanoparticles (PbO NPs), which are emitted to the environment by high-temperature technological processes, heavily impairs target organs. These nanoparticles pass through the lung barrier and are distributed via the blood into secondary target organs, where they cause numerous pathological alterations. Here, we studied in detail, macrophages as specialized cells involved in the innate and adaptive immune response in selected target organs to unravel their potential involvement in reaction to subchronic PbO NP inhalation. In this context, we also tackled possible alterations in lipid uptake in the lungs and liver, which is usually associated with foam macrophage formation. RESULTS: The histopathological analysis of PbO NP exposed lung revealed serious chronic inflammation of lung tissues. The number of total and foam macrophages was significantly increased in lung, and they contained numerous cholesterol crystals. PbO NP inhalation induced changes in expression of phospholipases C (PLC) as enzymes linked to macrophage-mediated inflammation in lungs. In the liver, the subchronic inhalation of PbO NPs caused predominantly hyperemia, microsteatosis or remodeling of the liver parenchyma, and the number of liver macrophages also significantly was increased. The gene and protein expression of a cholesterol transporter CD36, which is associated with lipid metabolism, was altered in the liver. The amount of selected cholesteryl esters (CE 16:0, CE 18:1, CE 20:4, CE 22:6) in liver tissue was decreased after subchronic PbO NP inhalation, while total and free cholesterol in liver tissue was slightly increased. Gene and protein expression of phospholipase PLCβ1 and receptor CD36 in human hepatocytes were affected also in in vitro experiments after acute PbO NP exposure. No microscopic or serious functional kidney alterations were detected after subchronic PbO NP exposure and CD68 positive cells were present in the physiological mode in its interstitial tissues. CONCLUSION: Our study revealed the association of increased cholesterol and lipid storage in targeted tissues with the alteration of scavenger receptors and phospholipases C after subchronic inhalation of PbO NPs and yet uncovered processes, which can contribute to steatosis in liver after metal nanoparticles exposure.
Keywords: kovové nanočástice; Humans; oxidy; Macrophages; Inflammation; Cholesterol; Lead; Oxides; Metal Nanoparticles; olovo; makrofágy; cholesterol; lidé; Type C Phospholipases; fosfolipasy typu C; zánět